ANALISIS NILAI INDEKS KEHIJAUAN (NDVI) PADA POLA RUANG KOTA AMBON, PROVINSI MALUKU - Jan Willem Hatulesila; Gun Mardiatmoko; Irwanto Irwanto (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2019)
Green Open Space is a component of landscaping that greatly affects urban air both directly and indirectly. The ideal standard minimum area of ​​green open space is at least 30% of the total area of ​​the city.The study used a spatial analysis method through the approach to calculating the Normalized Difference Vegetation Index (NDVI) for vegetation cover. Overlay analysis of GIS vegetation cover maps with the Ambon city spatial pattern map, has produced a map of the city green open spatial model, which shows a picture of existing corridors of green open space patterns, building spatial patterns, and non-vegetation spatial patterns (vacant land) .The results of the analysis of the green open space model map recommend the need for areas with urban park areas, park spots areas, and tree corridor areas planted on either side of the road. Inventory method, analysis of spatial and observations carried out at nine sampling locations, showed that the location of Ambon City's green open space was ± 1.115.900 m2 or 111,59 ha, with cover of understorey vegetation (grasses and saplings) 16,31 ha. Estimated carbon content of understorey vegetation (grasses and saplings) 52,49 kg/ha and 883 kg/ha of pole and tree vegetation. Normalized Difference Vegetation Index (NDVI) in nine sampling locations of Ambon City's green open space, for the area of vegetation cover is 61.58 ha or 58.31%, building area 39.63 ha or 37.52% and vacant land 4.40 ha or 4.17%.